In silico studies on cytotoxicity and antitumoral activity of acetogenins from Annona muricata L - Fallon Adido, Houéfa Egidia; Silva Chagas, Cristian Kallahan; Ferreira, Gleison Gonçalves; Carmo Bastos, Mírian Letícia; Dolabela, Maria Fâni (Frontiers in Chemistry, 2023)
As life expectancy increases, the number of people affected by cancer is increasing. The available drugs still cause several adverse reactions, and it is important to look for less toxic drugs that act on resistant cancers. The present study evaluated the antitumor potential of acetogenins. Through a literature review, 44 acetogenins isolated from Annona muricata were selected and subjected to in silico studies to predict the physicochemical properties, pharmacokinetics (Preadmet and Admet lab), toxicity (Preadmet and Protox II) and molecular docking in caspase 3 (DockThor). For muricatacin, a literature review was carried out for antitumor activity and cytotoxicity. Only muricatacin met all physicochemical criteria, while all compounds showed high cutaneous and intestinal absorption (HIA), moderate permeability in Madin-Darby canine kidney and Caco2 cells, strongly bound plasma proteins, freely crossed the blood-brain barrier, inhibited CYP2C19, CYP2C9 and CYP3A4 and have an affinity for CYP3A4, being metabolized by it, an undesirable characteristic for antitumor drugs. All compounds were toxic in at least one model, while compound 28 was not carcinogenic in rats and mice. Compounds 13, 14, 15, 16, 17 and 28 were selected for molecular docking into Caspase 3. Docking showed hydrophobic interactions, hydrogen and covalent bonds performed to maintain the stability of caspase 3, and cis-uvariamicin IV stood out more through the energies and chemical bonds of this parameter. The chloroform fraction from the methanolic extract of the seeds showed activity against triple-negative breast cancer, both in vitro and in vivo, and only muricatacin has studies in which the antitumor activity was evaluated in vitro and showed to be very promising. In summary, muricatacin and cis-uvariamicin IV appear to be very promising as antitumors, especially cis-uvariamicin IV.